The Efficacy of Dutasteride and Green Tea Combination Towards Angiogenesis and Bleeding on BPH after TURP : Study their effect on VEGF, MVD and Hb - Eriawan Agung Nugroho; Rifki Muslim; Ignatius Riwanto; Soetojo Wirjo Pranoto (Chemical Engineering Diponegoro University, 2015)
ABSTRACT Objectives: to find the efficacy dutasteride and green tea in reducing hemorrhage on TURP patients and to evaluate the anti- angiogenesis effect. Methods: Double Blind Randomized Controlled Trial Post Test Only, with 80 samples, randomized into 4 groups: 1 control group and 3 treatment groups (P1 with 0.5 mg of dutasteride, P2 with a capsul of green tea, and P3 with combination of 0.5 mg dutasteride and a capsul green tea at least 14 days before TURP. We compared the ΔHb define the VEGF expression and MVD count to evaluate the angiogenesis changes between 4 groups. The difference is considered statistically significant with p<.05. Results: ΔHb (-0.40 + 0.246) pg/ml for control group, (-0.20 + 0.067) pg/ml for P1 group, (-0.18 + 0.081) pg/ml for P2 group, and (-0.14 + 0.092) pg/ml for P3 group. VEGF expression were (20.20 + 17.386), (12.90 + 15.509), (11.60 + 9.121), and (3.60 + 1.667) for control, P1, P2, and P3 group respectively. MVD count were (41.20 + 10.273), (32.75 + 9.318), (26.15 + 7.278), and (18.35 + 7.876) for control, P1, P2, and P3 group respectively. The result from between-subject effect tests showed statistically significant differences in ΔHb (p<0.001), VEGF expression (p<0.001), and MVD count (p<0.001). Dutasteride and green tea significantly reduce the hemorrhage during TURP by decreasing the MVD. Conclusion: Administration of 0.5 mg dutasteride and 725 mg of green tea, 14 days prior to TURP significantly reduce the hemorrhage during TURP (Δ Hb) by decreasing the MVD